Observing end-state comfort favorable actions does not modulate action plan recall - Seegelke, Christian (Frontiers in Psychology, 2015)
A large corpus of work demonstrates that observing other people’s actions activates corresponding motor representations in the observer by running an internal simulation of the observed action. Recent evidence suggests that recalled action plans reflect a plan of how the observer would execute that action (based on the specific motor representation) rather than a plan of the actually observed action (based on the visual representation). This study examined whether people would recall an action plan based on a visual representation if the observed movement is biomechanically favorable for their own subsequent action. Participants performed an object manipulation task alongside a confederate. In the intra-individual task, the participant (or confederate) transported a plunger from an outer platform of fixed height to a center target platform located at different heights (home-to-target move), and then the same person transported the plunger back to the outer platform (target-back-to-home move). In the inter-individual task, the sequence was split between the two persons such that the participant (or confederate) performed the home-to-target move and the other person performed the target-back-to-home move. Importantly, the confederate always grasped the plunger at the same height. This grasp height was designated such that if participants would copy the action (i.e., grasp the object at the same height) it would place the participant’s arm in a comfortable position at the end of the target-back-to-home move (i.e., end-state comfort). Results show that participants’ grasp height was inversely related to center target height and similar regardless of direction (home-to-target vs. target-back-to-home move) and task (intra- vs. inter-individual). In addition, during the inter-individual task, participant’s target-back-to-home grasp height was correlated with their own, but not with the confederate’s grasp height during the home-to-target moves. These findings provide evide